Sinergisitas Humas dan Media Jurnalistik Dalam Meningkatkan Citra Kerjasama PT. Grand Mecca Holidays dengan Kementrian Agama Sumatera Utara Melalui Penyediaan Jasa Ibadah Umroh dan Haji - Muhammad Denis Alhilal; M. Yoserizal Saragih (LPPM Institut Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the Synergisity of Public Relations and Journalistic Media in enhancing PT. Grand Mecca Holidays together with the Ministry of Religion of North Sumatra through the provision of Umrah and Hajj services. The community is also assisted by PT, Grand Mecca Holidah's Public Relations and Journalistic Media activities for the Ministry of Religion of North Sumatra in carrying out Religious Worship activities in the Holy Land officially and recognized by the state. It is hoped that the collaboration between the two parties will continue to make it easier for the people to go to the Holy Land. The research method used is descriptive qualitative method with data collection techniques using primary data through observation and in-depth interviews with a Public Relations officer of PT. Grand Mecca Holidays and one of the users or pilgrims of the Umrah worship travel service. The results showed that the Synergy of Public Relations and Journalistic Media of PT. Grand Mecca Holidays has a way of trying to maintain good cooperation with the Ministry of Religion of North Sumatra in getting users of Umrah and Hajj travel services. So that they can continue to be committed to the Ministry of Religion of North Sumatra. The results of this study are expected to provide insight to the public and other travel providers of Umrah and Hajj services to be able to increase cooperation with companies or other institutions through journalistic and public relations media. Keywords: synergy, public relations, media journalism.